Nutritional needs of elite endurance athletes. Part I: Carbohydrate and fluid requirements - Tarnopolsky, M. A.; Gibala, M. J.; Jeukendrup, A. E.; Phillips, S. M. (European Journal of Sport Science, 2005)
Both carbohydrate depletion and dehydration have been shown to decrease performance whilst severe dehydration can also cause adverse health effects. Therefore carbohydrate and fluid requirements are increased with exercise. Ingestion of 200-300 g of CHO 3-4 h prior to exercise is an effective strategy in order to meet daily CHO demands and increase CHO availability during the subsequent exercise period. There is little evidence that CHO during the hour immediately prior to exercise has adverse effects such as rebound hypoglycaemia. CHO ingestion during exercise has been shown to improve performance as measured by enhanced work output or decreased exercise time to complete a fixed amount of work. Recent studies have demonstrated that exogenous CHO oxidation rates can be increased by ingesting combinations of CHO that use different intestinal CHO transporters. After exercise maximal muscle glycogen re-synthesis rates can be achieved by ingesting CHO at a rate of 1.2 g/kg/h, in relatively frequent (e.g., 15-30 min) intervals for up to 5 h following exercise. Protein amino acid mixtures may increase glycogen synthesis further but only if relatively small amounts of CHO are ingested.